Majorana fermions - Medic, Luka (Matrika, 2019)
The article presents Majorana modes in condensed matter physics. The Kitaev chain model with a p-wave superconductor pairing is approached and Majorana operators are introduced. Step by step topological protection, non-abelian statistics and braiding, key ingredients for topological quantum computation, are presented. The theoretical Kitaev model is modified to a realistic spinful fermion nanowire model with s-wave superconductor induced pairing and spin-orbit coupling. Lastly, experimental evidence is presented.
Keywords: condensed matter physics; fizika kondenzirane snovi; Kitaev chain model; Kitaev model verige; kvantno računalništno; Majorana fermioni; Majorana fermions; quantum computation